2010
DOI: 10.1002/wrna.28
|View full text |Cite
|
Sign up to set email alerts
|

The roles of TTP and BRF proteins in regulated mRNA decay

Abstract: AU-rich element (ARE) motifs are cis-acting elements present in the 3′UTR of mRNA transcripts that encode many inflammation-and cancer-associated genes. The TIS11 family of RNA-binding proteins, composed of TTP, BRF-1, and BRF-2 play a critical role in regulating the expression of ARE-containing mRNAs. Through their ability to bind and target ARE-containing mRNAs for rapid degradation, this class of RNA-binding proteins serves a fundamental role in limiting the expression of a number of critical genes, thereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
154
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(159 citation statements)
references
References 119 publications
2
154
0
3
Order By: Relevance
“…TTP regulates the expression of ARE-containing mRNAs by both promoting the degradation and repressing the translation of target mRNA (38). While the mechanisms by which TTP promotes the degradation of ARE-containing mRNAs have been extensively studied (39), the mechanism underlying TTP-mediated translational repression is not so well established. A difficulty in the studies on TTP repression of translation is that the magnitude of inhibition is relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…TTP regulates the expression of ARE-containing mRNAs by both promoting the degradation and repressing the translation of target mRNA (38). While the mechanisms by which TTP promotes the degradation of ARE-containing mRNAs have been extensively studied (39), the mechanism underlying TTP-mediated translational repression is not so well established. A difficulty in the studies on TTP repression of translation is that the magnitude of inhibition is relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…2A, upper left), indicating that Tob2 proteins can be phosphorylated to different extents. As a control, we showed that AP pretreatment of TTP, an ARE-binding protein known to be highly phosphorylated (Tiedje et al 2010;Sanduja et al 2011), effectively removed its phosphates. It is worth noting that the relative mobilities and intensities of the three bands for Tob2-FF differ from those for WT Tob2, suggesting a link between its phosphorylation state and its ability to interact with PABPC1.…”
Section: Phosphorylation Of Tob2 and Its Ability To Interact With Pabpc1mentioning
confidence: 98%
“…In support of this idea, one genome-wide screen found that 85% of the 380 RBPs examined were expressed in the embryonic (E13.5) and early postnatal (P0) mouse brain (McKee et al 2005). Most notable are the well-described RBPs that regulate various stages of mRNA metabolism and are important for proper neuronal differentiation and/or function, such as butyrate-response factor 1 (BRF1) (Sanduja et al 2011), neuro-oncologic ventral antigens 1/2 (NOVA 1/2) (Darnell 2006), A +U binding factor 1 (AUF1) (Gratacos and Brewer 2010), tristetraprolin (TTP) (Sanduja et al 2011), K homology splicing regulatory protein (KSRP) (Briata et al 2012), and Hu/embryonic lethal abnormal vision-like (ELAVl) ( Table 1; Pascale et al 2008). The majority of RBPs can be clustered according to their similar molecular functions, such as those belonging to the translation and turnover regulatory (TTR)-RBP group.…”
Section: Introductionmentioning
confidence: 99%